Effects of adding morphine to intra-articular dexamethasone injection on postoperative pain after arthroscopic subacromial decompression shoulder surgery - Sameh H Seyam; Khaled Elsheshtawy; Mofeed A Abdelmaboud (Wolters Kluwer Medknow Publications, 2019)
Background Arthroscopic shoulder surgery is a common method in the surgical treatment of shoulder diseases. We compared a combination of dexamethasone-bupivacaine-morphine against bupivacaine-morphine, as well as bupivacaine alone following arthroscopic subacromial decompression surgery. The study aimed for better quality of postoperative analgesia and lower pain intensity. Patients and methods This prospective, randomized, double-blinded controlled study was conducted on 60 patients undergoing arthroscopic shoulder subacromial decompression surgery. The patients were randomly allocated into three equal groups. All medications were injected intra-articularly at the end of the procedure. In the control group, 10 ml of 0.5% bupivacaine+5 ml isotonic saline (total volume, 15 ml) were injected. In the morphine group, 5 mg morphine diluted in 5 ml normal saline+10 ml of 0.5% bupivacaine was injected. In the morphine-dexamethasone group, 5 mg morphine+400 μg/kg weight dexamethasone completed to 5 ml with normal saline+10 ml of 0.5% bupivacaine was injected. Visual analog score, vital signs, time of first analgesic request, need for supplemental analgesic, and adverse effects were recorded. Results The morphine-dexamethasone group showed a lower visual analog score at rest and movement, delayed time for first analgesic request, more stable vital signs, and less adverse effects as compared with the other groups. Conclusion Addition of intra-articular morphine to dexamethasone and bupivacaine has a remarkable analgesic efficacy, a much-prolonged postoperative pain control, minimal postoperative analgesic requirement, and better patient compliance with minimal side effects.